2011
DOI: 10.1126/science.1207502
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Dependent Long-Term Depression of Electrical Synapses

Abstract: Use-dependent forms of synaptic plasticity have been extensively characterized at chemical synapses, but a relationship between natural activity and strength at electrical synapses remains elusive. The thalamic reticular nucleus (TRN), a brain area rich in gap-junctional (electrical) synapses, regulates cortical attention to the sensory surround and participates in shifts between arousal states; plasticity of electrical synapses may be a key mechanism underlying these processes. We observed long-term depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
190
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(201 citation statements)
references
References 41 publications
10
190
1
Order By: Relevance
“…Indeed, the bimodal shape of the cross-correlation function is an important criterion for judging whether two neurons are connected by gap-junction (Brivanlou et al 1998;DeVries 1999;Shlens et al 2008). In a few cases (21 out of 108 neuronal pairs recorded), the cross-correlation may only have a single peak around zero lag due to one-way signal transmission via gap-junction (Haas et al 2011;MannMetzer and Yarom 1999). Note that asymmetric correlations do not necessarily imply asymmetric conductance, and they may occur due to asymmetric input resistances.…”
Section: Correlation Patterns Of Rgcsmentioning
confidence: 99%
“…Indeed, the bimodal shape of the cross-correlation function is an important criterion for judging whether two neurons are connected by gap-junction (Brivanlou et al 1998;DeVries 1999;Shlens et al 2008). In a few cases (21 out of 108 neuronal pairs recorded), the cross-correlation may only have a single peak around zero lag due to one-way signal transmission via gap-junction (Haas et al 2011;MannMetzer and Yarom 1999). Note that asymmetric correlations do not necessarily imply asymmetric conductance, and they may occur due to asymmetric input resistances.…”
Section: Correlation Patterns Of Rgcsmentioning
confidence: 99%
“…Activity-dependent plasticity of electrical synapses is an increasingly important theme in neuroscience (Haas et al, 2011;Hestrin, 2011;Landisman and Connors, 2005;Pereda et al, 2004;Zsiros and Maccaferri, 2008) and it is important to increase our understanding of how modulating the strength of electrical synapses can optimize the signal processing in the CNS. The gap junction coupling between neurons (and many other cells) is mediated by specialized channel proteins termed connexins (reviewed by Söhl et al, 2005) where post-translational modification by phosphorylation can modulate important functional properties (reviewed by Moreno and Lau, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In this model comprised of neurons connected only through gap junctions, the coupling coefficient between neurons was Ïł0.3, which is somewhat higher than experimental measures of Ïł0.1 (e.g., Haas et al 2011). We then reduced this coefficient to 0.1 (through a 10-fold increase in the mean resistance of the gap junctions) and found that a concomitant increase in the number of postsynaptic targets of each neuron (from 2 to 3) was required in order for sensory inputs to perturb locomotion.…”
Section: Extensive Distribution Of Sensory Inputsmentioning
confidence: 98%